I INFLUENCE OF HEAT TREATMENT ON MACROMYCETE PHYSICAL CHARACTERISTICS AND THE CONTENT OF HEAVY METALS IN THEM - Che S.N.; Bakaytis V.I.; Tsapalova I.E. (Техника и технология пищевых производств)
The relevance of the study is due to looking for ways to reduce the content of heavy metals in mushrooms, as several times excess oftheir maximum permissible concentrations is registered in macromycetes of the Siberian region. The article demonstrates the influence of heat treatment on physical characteristics (mass, volume, humidity) and the content of some mineral elements includin g heavy metals in mushrooms growing in the Novosibirsk region. It is shown that heat treatment of macromycetes causes a change in physical characteristics: mass and volume reduction, increase of humidity and decrease in the content of trace elements and h eavy metals. The rate of change of the studied characteristics is determined by the species of macromycetes and time of heat exposure. Results of studies have shown that reducing the mass and volume of macromycetes does not lead to an increase in the concentration of heavy metals. When cooking mushrooms for 10 minutes the amount of mineral elements is reduced by 17-66%; for a 20 minute period this characteristic is 1.5-3.0 times less with the greatest losses occurring in nickel and selenium, with both the white milkycapand the chanterelle. Research results proved that the heat treatment canbe considered as heavy metals detoxification factor in mush-rooms when the exposure time is not less than 20 minutes.